Evaluation of preoperative duloxetine use for postoperative analgesia following laparoscopic cholecystectomy: a randomized controlled trial - Mansour, Noha O.; Boraii, Sherif; Elnaem, Mohamed Hassan Abdelaziz; Elrggal, Mahmoud E.; Omar, Tamer; Abdelraouf, Amr; Abdelaziz, Doaa H. (Frontiers Media S.A., 2022)
Background: The pain pattern after laparoscopic cholecystectomy (LC) is complex and distinct from postoperative pain after other laparoscopic procedures, suggesting that procedure-specific optimal analgesic management plans should be proposed. Duloxetine, a non-opioid neuromodulator, has been widely used to manage pain with dual central and peripheral analgesic properties.